Microstructure, Mechanical, Tribological and Synergistic strengthening mechanisms of nickel/graphene nanoplatelets hybrid reinforced AZ91D magnesium-based matrix composites via spark plasma sintering - Olugbenga Ogunbiyi; Samuel A. Iwarere; Rotimi Sadiku; Michael O. Daramola (Journal of Materials Research and Technology, 2024)
AZ91D-Ni-graphene nanoplatelets (GNPs) Mg-based composites were effectively consolidated using spark plasma sintering (SPS). The - reinforcement in the AZ91D Mg alloy varies from 0 wt% to 2 wt%, with Ni constituent fixed at 1.5 wt%. Scanning electron microscope, Transmission electron microscope, X-ray diffraction and Raman spectroscopy were utilised to investigate the morphology of the powder and sintered compact. The synergistic strengthening offered by the inclusion of GNPs comprising grain refinement (ΔσHall−Petch), load transfer from AZ91D-Ni Mg-based alloy matrix to GNPs reinforcement (ΔσLT), dislocations strengthening due to the mismatch in the coefficient of thermal expansion (CTE)(ΔσCTE), modulus mismatch (Δσmm), and strengthening due to Orowan (Δσorowan) was investigated. Experimental results indicate that the addition of GNPs contributes minimally to the densification of the compacts, increasing from 97% to 98.1% with increasing GNPs. However, significant improvements were obtained for other properties investigated, such as a microhardness, which increased from 67.4 to 89.7 H V, nano hardness from 4744.9 to 18,251.3 MPa, an elastic modulus from 84.53 to 243.75 GPa and wear rate from 5.21 × 10−3 to 3.85 × 10−3 mm3/N/m under 10 N load with an increase in GNPs content. This study establishes the capability of GNPs as efficient reinforcement in manufacturing metal matrix composites with enhanced mechanical and tribological properties.